2020
DOI: 10.1007/s10143-020-01340-0
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes insipidus and syndrome of inappropriate antidiuresis (SIADH) after pituitary surgery: incidence and risk factors

Abstract: Hintergrund/FragestellungElektrolytstörungen in Folge eines operativen Eingriffs an der Hypophyse sind häufige und ernstzunehmende Komplikationen, welche mit verlängerter Hospitalisationsdauer beziehungsweise erneuter Hospitalisierung, intensivmedizinischer Betreuung und somit verzögerter postoperativer Erholung einhergehen. Diabetes Insipidus (DI) und verzögerte symptomatische Hyponatriämie (DSH) sind postoperativ die häufigsten frühen endokrinen Komplikationen, wobei «Syndrome of Inappropriate Antidiuresis» … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
35
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 48 publications
4
35
1
Order By: Relevance
“…Previous studies reported that the incidence rate of delayed hyponatremia after TSS for pituitary adenomas is between 4% and 23% (6). The main clinical manifestation of SIADH is delayed hyponatremia due to the uncontrolled release of antidiuretic hormone secretion (ADH) following damage to the hypothalamus-neurohypophyseal system, leading to water retention.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies reported that the incidence rate of delayed hyponatremia after TSS for pituitary adenomas is between 4% and 23% (6). The main clinical manifestation of SIADH is delayed hyponatremia due to the uncontrolled release of antidiuretic hormone secretion (ADH) following damage to the hypothalamus-neurohypophyseal system, leading to water retention.…”
Section: Discussionmentioning
confidence: 99%
“…We identified predictors of delayed hyponatremia that are different from those reported previously. Age (young and old) has been identified as a predictor of postoperative delayed hyponatremia (3,6,13). Moreover, owing to the sex-specific difference in the response to antidiuretic hormone, women are more likely than men to develop postoperative delayed hyponatremia (14).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, measurements of postoperative AVP (Table 4) also indicated no signi cant differences for AVP values (p = 0.440) and no excess production of AVP, such as SIADH. Thus, prediction of individual patient risk for DI or SIADH remains di cult [34].…”
Section: Discussionmentioning
confidence: 99%